NbPt3 Intermetallic Nanoparticles: Highly Stable and CO‐Tolerant Electrocatalyst for Fuel Oxidation. Issue 4 (30th January 2014) - Ramesh, Gubbala V.; Kodiyath, Rajesh; Tanabe, Toyokazu; Manikandan, Maidhily; Fujita, Takeshi; Matsumoto, Futoshi; Ishihara, Shinsuke; Ueda, Shigenori; Yamashita, Yoshiyuki; Ariga, Katsuhiko; Abe, Hideki
Abstract NbPt3 intermetallic nanoparticles (NbPt3 NPs) are synthesized for the first time, and their electrocatalytic performance towards fuel oxidation is tested. Chemical reduction of dichloro(1, 5‐cyclooctadiene)platinum(II) and niobium(V) pentachloride in dry diglyme with a superhydride, followed by annealing, yields the desired NbPt3 NPs. These NbPt3 NPs exhibit higher stability than pure Pt NPs during repeated electrochemical cycles in H2SO4. The NbPt3 NPs are less susceptible to CO adsorption compared with Pt NPs and exhibit improved catalytic activity towards the electrooxidation of ethanol and/or formic acid. These NbPt3 NPs are promising candidates as electrode catalysts in fuel cells.